Evidences of Herbal Medicine-Derived Natural Products Effects in Inflammatory Lung Diseases - Fernanda Paula R. Santana; Nathalia M. Pinheiro; Márcia Isabel B. Mernak; Renato F. Righetti; Mílton A. Martins; João H. G. Lago; Fernanda D. T. Q. dos Santos Lopes; Iolanda F. L. C. Tibério; Carla M. Prado (Mediators of Inflammation)
Pulmonary inflammation is a hallmark of many respiratory diseases such as asthma, chronic obstructive pulmonary disease (COPD), and acute respiratory syndrome distress (ARDS). Most of these diseases are treated with anti-inflammatory therapy in order to prevent or to reduce the pulmonary inflammation. Herbal medicine-derived natural products have been used in folk medicine and scientific studies to evaluate the value of these compounds have grown in recent years. Many substances derived from plants have the biological effects in vitro and in vivo, such as flavonoids, alkaloids, and terpenoids. Among the biological activities of natural products derived from plants can be pointed out the anti-inflammatory, antiviral, antiplatelet, antitumor anti-allergic activities, and antioxidant. Although many reports have evaluated the effects of these compounds in experimental models, studies evaluating clinical trials are scarce in the literature. This review aims to emphasize the effects of these different natural products in pulmonary diseases in experimental models and in humans and pointing out some possible mechanisms of action.